Preemptive use of anti-inflammatories and analgesics in oral surgery: a review of systematic reviews - Pimenta, Régis Penha; Takahashi, Cristiane Midori; Barberato-Filho, Silvio; McClung, Delaine Cristina Ferreira; Moraes, Fabio da Silva; de Souza, Isabela Muniz; Bergamaschi, Cristiane de Cássia (Frontiers in Pharmacology, 2024)
Objectives: This review of systematic reviews evaluated the effectiveness and safety of the preemptive use of anti-inflammatory and analgesic drugs in the management of postoperative pain, edema, and trismus in oral surgery. Materials and methods: The databases searched included the Cochrane Library, MEDLINE, EMBASE, Epistemonikos, Scopus, Web of Science, and Virtual Health Library, up to March 2023. Pairs of reviewers independently selected the studies, extracted the data, and rated their methodological quality using the AMSTAR-2 tool. Results: All of the 19 studies reviewed had at least two critical methodological flaws. Third molar surgery was the most common procedure (n = 15) and the oral route the most frequent approach (n = 14). The use of betamethasone (10, 20, and 60 mg), dexamethasone (4 and 8 mg), methylprednisolone (16, 20, 40, 60, 80, and 125 mg), and prednisolone (10 and 20 mg) by different routes and likewise of celecoxib (200 mg), diclofenac (25, 30, 50, 75, and 100 mg), etoricoxib (120 mg), ibuprofen (400 and 600 mg), ketorolac (30 mg), meloxicam (7.5, 10, and 15 mg), nimesulide (100 mg), and rofecoxib (50 mg) administered by oral, intramuscular, and intravenous routes were found to reduce pain, edema, and trismus in patients undergoing third molar surgery. Data on adverse effects were poorly reported. Conclusion: Further randomized clinical trials should be conducted to confirm these findings, given the wide variety of drugs, doses, and routes of administration used.